2022
DOI: 10.1002/lary.30242
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Inhaled Fosamprenavir Reverses Pepsin‐Induced Damage in a Laryngopharyngeal Reflux Mouse Model

Abstract: Objective More than 20% of the US population suffers from laryngopharyngeal reflux. Although dietary/lifestyle modifications and alginates provide benefit to some, there is no gold standard medical therapy. Increasing evidence suggests that pepsin is partly, if not wholly, responsible for damage and inflammation caused by laryngopharyngeal reflux. A treatment specifically targeting pepsin would be amenable to local, inhaled delivery, and could prove effective for endoscopic signs and symptoms associated with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 138 publications
(330 reference statements)
0
19
0
Order By: Relevance
“…We recently identified an HIV protease inhibitor (amprenavir, commonly administered as fosamprenavir) which binds and inhibits pepsin in the nanomolar range and rescued histologic indications of peptic injury in a mouse LPR model. 54 Many LPR episodes are weakly acidic and weakly acidic pepsin elicits microscopically evident cell dissociation in vitro 43 akin to dilated intercellular spaces which are a hallmark of LPR and GERD.…”
Section: Discussionmentioning
confidence: 99%
“…We recently identified an HIV protease inhibitor (amprenavir, commonly administered as fosamprenavir) which binds and inhibits pepsin in the nanomolar range and rescued histologic indications of peptic injury in a mouse LPR model. 54 Many LPR episodes are weakly acidic and weakly acidic pepsin elicits microscopically evident cell dissociation in vitro 43 akin to dilated intercellular spaces which are a hallmark of LPR and GERD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant correlation of decreased distal esophageal MNBI with an increased number of proximal acidic impedance events, as seen in Table II, would favor the reflux theory. The lack of differences in pharyngeal MNBI be explained by the majority of pharyngeal reflux events being weakly acidic or non‐acidic as they are brief and quickly buffered by salivary bicarbonate and compensatory swallowing 28 . Sakin et al 29 found that patients with LPR symptoms had a significantly decreased pharyngeal MNBI compared to patients with GERD without LPR symptoms, despite a similar pharyngeal reflux rate on impedance monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of differences in pharyngeal MNBI be explained by the majority of pharyngeal reflux events being weakly acidic or non-acidic as they are brief and quickly buffered by salivary bicarbonate and compensatory swallowing. 28 Sakin et al 29 found that patients with LPR symptoms had a significantly decreased pharyngeal MNBI compared to patients with GERD without LPR symptoms, despite a similar pharyngeal reflux rate on impedance monitoring. Although there were no control subjects included in the study, the decreased pharyngeal MNBI in LPR versus GERD patients would demonstrate chronic reflux into the hypopharynx, as described in the reflux theory.…”
Section: Discussionmentioning
confidence: 99%
“…The IC50 of amprenavir for porcine pepsin (3.56 uM) was determined in a prior study [ 37 ]. The dose for study herein was selected based upon the serum concentration observed in patients taking the manufacturer-recommended dose for the treatment of HIV [ 90 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our group recently identified the HIV protease inhibitor, amprenavir, as a potential pepsin-targeting therapeutic for laryngopharyngeal reflux (LPR). Amprenavir inhibited pepsin at low micromolar concentrations and its prodrug fosamprenavir prevented histologic changes in an LPR mouse model [ 37 ]. In parallel work, we found that pepsin was required for esophageal and laryngeal epithelial barrier disruption at pH4 and that amprenavir preserved laryngeal epithelial integrity and prevented damage to a critical cell adhesion molecule elicited by pepsin at pH4 [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%